THE INFLUENCE OF DIGITAL LITERACY AND SOCIAL MEDIA PROMOTION ON MARKETING PERFORMANCE WITH DIGITAL READINESS AS A MODERATING VARIABLE IN SMALL AND MEDIUM ENTERPRISES IN CIREBON - Sholihin Sholihin; Aang Curatman; Jefry Romdonny (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of digital literacy and social media promotion on the marketing performance of Small and Medium Enterprises (SMEs) in Cirebon, with digital readiness as a moderating variable. The research adopts a quantitative approach using a survey method involving 325 SME owners registered at Rumah UMKM Cirebon. Data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling with the Partial Least Squares approach. The findings reveal that digital literacy and social media promotion have a positive effect on the marketing performance of SMEs, which is reflected in increased sales growth and wider market reach. The research model is able to explain more than half of the variation in SME marketing performance. However, digital readiness has not demonstrated a significant moderating role in strengthening the relationship between digital literacy, social media promotion, and marketing performance. This study has several limitations, particularly its focus on a specific region and type of business. Therefore, future research is recommended to expand the scope of the study to different regions and include additional strategic variables that may influence SME marketing performance. Keywords: Digital Literacy; Social Media Promotion; Marketing Performance; SMEs